Orbital-scale hydroclimate variations in the southern Tibetan Plateau over the past 414, 000 years. (1st September 2022) - Wang, Haibo; Wang, Xianyan; Pérez-Mejías, Carlos; Li, Youwei; Li, Hanying; Cai, Yanjun; Zhang, Haiwei; Han, Jian'en; Duan, Pengzhen; Lu, Jiayu; Ning, Youfeng; Edwards, R. Lawrence; et al.
Abstract: Speleothem oxygen isotope (δ 18 O) constitutes one of key proxies to reconstruct the Indian and East Asian summer monsoon (ISM and EASM) hydroclimate history on a wide range of timescales. Here, we use three new well-dated speleothem δ 18 O records from Tianmen cave, in the south-central Tibetan Plateau (TP), together with previous records from the same cave, to reconstruct a composite Tianmen record spanning over the past 414, 000 years. The Tianmen δ 18 O record follows Northern Hemisphere summer insolation (NHSI), broadly coherent with speleothem δ 18 O records from both ISM and EASM regimes. In comparison with previous model simulations and modern hydroclimate analyses, the Tianmen δ 18 O was interpreted primarily as a proxy indicating the ISM intensity. The Tianmen δ 18 O record comprises both high and low NHSI time periods, which reveals an exceptional large amplitude (∼14‰) of δ 18 O variations at the precession band, possibly resulted from a combination effect of precipitation amount, moisture source, transport pathway, high elevation and rainout. Besides, a broad consistency on orbital-scale variability among Tianmen δ 18 O, δ 13 C and trace element records is found, suggesting that the ISM intensity regulates the effective rainfall at the cave site as well. Notably, Tianmen speleothem growth occurred merely during warm-wet interglacial periods, even during low NHSI times near the precession maximum, and in contrast, hiatuses persistently occurred throughout cold-dry glacial periods. This pattern is similar to that found in travertine formations in the region, both suggesting that the interglacial temperature might be a prerequisite for speleothem/travertine formations in the region, while the strong ISM precipitation in turn provides a sufficient condition. Our new Tianmen record, combined with a large set of speleothem records from both Asian Westerlies and Asian monsoon domains, gives further evidence to reinforce a previous hypothesis: a consistent temporal pattern in the δ 18 O of precipitation on orbital and millennial scales over the vast Asian monsoon and Westerlies regimes. As such, in order to reconcile the precipitation δ 18 O variations between speleothem and TP ice cores, we argue that the Guliya ice-core chronology may have a basal age of ∼70 ka BP, which is supported by recent dating results from the Guliya ice cap. Highlights: Speleothem δ 18 O records from the south-central Tibetan Plateau primarily indicate the Indian summer monsoon (ISM) intensity. Combined effect results in a large amplitude (∼14‰) of Tianmen cave δ 18 O variations at the precession band. Interglacial temperature and high ISM precipitation are critical factors for the speleothem formations in the region.